Structural Relation of Export Assistance Programme and Export Performance Determinants: A Study of Handloom Industry. Issue 2 (December 2021) - Singh, Vishal Kumar; Gautam, Amit
This study focuses on export assistance determinants and qualitative export performance determinants of the handloom industry. Additionally, the effect of export assistance needs to check on export performance determinants. The study found the determinants from the extensive literature review. A model is proposed based on identified determinants, and the hypotheses developed accordingly. Initially, first-order CFA is applied for validity measures and then second-order CFA due to presence of multicollinearity among the determinants. Second-order CFA analyses the combined effect of all studied determinants with the help of structural equation modelling. The four determinants of export assistance and five determinants of export performance are identified from the extensive literature. The financial support construct influences the export assistance majorly that is represented through high correlation coefficient and mixed response for other determinants. Overall, the combined effect of export assistance is positive on export performance determinants. There is a need to establish the functions of various export assistances based on their characteristics, and this study helps in operational classification of assistance based on identified determinants. Additionally, the impact of individual assistance can measure the changes in the export performance determinants of the handloom industry.